Effect of coating pigment type on paper printability with water-based inks - ÖZCAN, ARİF; SÖNMEZ, SİNAN; TUTAK, DOĞAN (My University, 2022)
Nowadays, the need for papers and cardboards with improved surface properties is increasing with the development of the packaging industry. The improvements made are not only limited to the paper and paper surface, but also environmentalist approaches are exhibited in printing ink. For this purpose, the use of water-based ink tends to become widespread, especially in food packaging. In this study, five different paper coating formulations were prepared using different proportions of precipitated calcium carbonate (PCC) and kaolin pigments. Latex (Acronal S360D) was used as a binder. All prepared coating mixes were applied onto the base paper surface. All coated papers were also subjected to the calendering process. In addition, three different dyestuffs (14, 17, 20%) concentrations of water-based printing inks were prepared. Prints were made by the silk screen printing technique on the calendered-coated papers. The optical and physical properties (roughness, air permeance, paper gloss and printing gloss, contact angle and surface energy) of all papers were measured according to the standards. Paper gloss, print gloss, Delta E-00 color differences, contact angles and surface energy measurements were made, and the effects of dye ratio on printing and gloss in water-based inks and coating type suitable for printability were investigated. As a result, papers can be coated and even calendered to achieve better paper surface properties and printability. In the case of printing with water-based inks, better printability properties are obtained by choosing PCC pigmented coated papers.
Keywords: Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); MALZEME BİLİMİ, KAPLAMALAR VE FİLMLER; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); MATERIALS SCIENCE, COATINGS & FILMS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Chemistry (miscellaneous); General Materials Science; General Chemistry; Process Chemistry and Technology; Physical Sciences; Printability; Paper coating; Water-based inks; Calcium carbonate; Kaolin; INKJET; POLYURETHANE; STARCH; Printability; Paper coating; Water-based inks; Calcium carbonate; Kaolin